Power System Grid Planning with Distributed Generation - Kakaza, Mnikeli (Department of Electrical Engineering, 2022)
Distributed Generation (DG) is one of the technologies approved by the South African government for the country's generation expansion to meet future load demand and to support economic growth. DGs change the conventional power flow (generation, transmission to distribution) by injecting real and reactive power at distribution voltage levels. The change in the conventional power flow creates complexity in the power system grid planning due to the conversion of the power system from a passive network to an active network. Introduction of bi-directional power flow on the power system can, among other benefits reduce local power demand which opens opportunities for capital investment deferrals on the transmission and distribution sectors. Consequently, DG impact on the transmission and distribution grid planning has been studied by other researchers. However, previous studies evaluated DG integration on a regulated market and assumed a certain level of generation availability during network peaking period. None of the studies have yet evaluated the benefits on an unregulated market using real measured data. Furthermore, SA distribution network expansion is also being planned without incorporating DGs on the network because of unreliability of wind and solar energy and the network operator's inability to influence the size, location and penetration level of DGs. This planning approach forces the network operator to do more to ensure high network strength. This approach can also result in network overdesign and unnecessary capital expenditure due to the potential benefits that can be deduced from DGs. This dissertation therefore aims to investigate whether incorporating future DG integration in distribution network planning can alleviate financial ramifications of grid code compliance requirements. The data used in the simulations was obtained from the distribution network operator and comprises of both real and reactive power values with a sampling time of 60 minutes for a period of a year. Simulations were conducted for both low and high load conditions to cover the extreme ends of the network and the parameters that were assessed are thermal rating, voltage regulation and network grid losses. Results showed that thermal constraints that are expected on the network when DGs are not considered are not evident when DGs are considered. Results further revealed that there are undervoltage improvements on the network when DGs are considered, and this reduces the capital expenditure that would have otherwise been incurred without DGs to result in a grid code compliant network. Furthermore, there is evidence of reduction in losses under high load conditions and increase in losses under low load conditions in the simulation results. Reduction in losses is caused by supplementary generation from wind and solar plants while increase in losses is due to excessive generation from wind plants which necessitate transportation over long distances to the nearest load centres. In addition to location, size and penetration levels as described in the literature, technology selection for a particular load type is also of utmost important to maximise the DG benefits on the network.